Classifying β-Barrel Assembly Substrates by Manipulating Essential Bam Complex Members - Mahoney, Tara F. (J Bacteriol, 2016)
The biogenesis of the outer membrane (OM) of Escherichia coli is a conserved and vital process. The assembly of integral β-barrel outer membrane proteins (OMPs), which represent a major component of the OM, depends on periplasmic chaperones and the heteropentameric β-barrel assembly machine (Bam complex) in the OM. However, not all OMPs are affected by null mutations in the same chaperones or nonessential Bam complex members, suggesting there are categories of substrates with divergent requirements for efficient assembly. We have previously demonstrated two classes of substrates, one comprising large, low-abundance, and difficult-to-assemble substrates that are heavily dependent on SurA and also Skp and FkpA, and the other comprising relatively simple and abundant substrates that are not as dependent on SurA but are strongly dependent on BamB for assembly. Here, we describe novel mutations in bamD that lower levels of BamD 10-fold and >25-fold without altering the sequence of the mature protein. We utilized these mutations, as well as a previously characterized mutation that lowers wild-type BamA levels, to reveal a third class of substrates. These mutations preferentially cause a marked decrease in the levels of multimeric proteins. This susceptibility of multimers to lowered quantities of Bam machines in the cell may indicate that multiple Bam complexes are needed to efficiently assemble multimeric proteins into the OM. IMPORTANCE The outer membrane (OM) of Gram-negative bacteria, such as Escherichia coli, serves as a selective permeability barrier that prevents the uptake of toxic molecules and antibiotics. Integral β-barrel proteins (OMPs) are assembled by the β-barrel assembly machine (Bam), components of which are conserved in mitochondria, chloroplasts, and all Gram-negative bacteria, including many clinically relevant pathogenic species. Bam is essential for OM biogenesis and accommodates a diverse array of client proteins; however, a mechanistic model that accounts for the selectivity and broad substrate range of Bam is lacking. Here, we show that the assembly of multimeric OMPs is more strongly affected than that of monomeric OMPs when essential Bam complex components are limiting, suggesting that multiple Bam complexes are needed to assemble multimeric proteins.